Inhibitory effect of cytotoxic nitrogen-containing heterocyclic stilbene analogues on VEGF protein secretion and VEGF, hTERT and c-Myc gene expression. Issue 10 (28th August 2015) - Martí-Centelles, Rosa; Murga, Juan; Falomir, Eva; Carda, Miguel; Alberto Marco, J.
Abstract : Twenty-one nitrogen-containing heterocyclic stilbenes were synthesized. Their cytotoxicity and effect on VEGF protein secretion as well as VEGF, hTERT and c-Myc gene expression were evaluated. Abstract : A group of 21 nitrogen-containing heterocyclic stilbene derivatives, prepared by means of Heck coupling reactions, has been investigated for their cytotoxicity as well as their ability to inhibit the production of the vascular endothelial growth factor (VEGF) and the activation of telomerase. The ability of these compounds to inhibit proliferation of two tumoral cell lines (HT-29 and MCF-7) and one non-tumoral cell line (HEK-293) was first determined. Subsequently, we determined the capacity of the compounds to inhibit the secretion of VEGF in the aforementioned cell lines and downregulate the expression of the VEGF, hTERT and c-Myc genes, of which the latter two are involved in controlling the activation of telomerase.